Comparative Evaluation of UMMI and At-Tartili Methods in Elementary Quranic Literacy Using the CIPP Model - Nurul Hidayah; Luk-Luk Nur Mufidah; Luluk Luluk Indarti (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2026)
The ability to read and write the Quran (BTQ) is an essential skill in elementary education, vital for cultivating a fluent and rhythmic generation of Quranic scholars. The UMMI and At-Tartili systems are two prevalent approaches, each emphasizing distinct aspects: reading fluency and accuracy. This study seeks to assess and contrast the efficacy of both methodologies utilizing the CIPP (Context, Input, Process, Product) evaluation model. A mixed-methods approach was used to gather data through observations, interviews, and student reading assessments at two madrasahs in Kediri Regency. The research findings indicate that the UMMI approach significantly enhances students' reading fluency and motivation, whereas the At-Tartili method demonstrates superiority in tajwid accuracy and reading quality. Context and input assessment indicated resource preparedness for method implementation; however, process elements require enhancement, especially in terms of learning differentiation. This discovery advocates for the creation of a hybrid model that amalgamates the advantages of both methodologies to enhance the efficacy and equilibrium of BTQ learning. This study advances the creation of an evidence-based Quranic learning model pertinent to madrasah education.